Jakarta: Kota Megah dengan Jurang Kesenjangan Sosial dan Ekonomi: Jakarta: A Grand City with a Deep Divide in Social and Economic Inequality - Graciovyn Christiano Tupan; Wilbert; Netta Wijaya; Klarissa; Scherika Tanaka; Kiky Soraya; Sukron Ma’Mun; Maureen Xaviera Sisley (Universitas Bojonegoro, 2025)
West Jakarta, as part of the Jakarta metropolitan area, illustrates a complex socio-economic dynamic marked by stark inequalities in access to basic services such as education, healthcare, digital technology, employment, and asset ownership. This study examines these disparities through qualitative research, utilizing direct interviews with residents from diverse social classes: a restaurant worker, an office employee, and a business owner. The findings reveal significant gaps in opportunities and living conditions between high-income and low-income groups, which result in limited social mobility and persistent economic vulnerability among underprivileged communities. The study highlights education and healthcare as the most urgent sectors requiring improvement to promote equal opportunities. To address this issue, collaboration among the government, the private sector, and civil society is essential. The recommendations include improving public service quality, providing education and health subsidies, expanding technology access, and implementing community-based economic empowerment programs. This research supports Sustainable Development Goal (SDG) 10 by emphasizing the importance of reducing inequality for building a fairer, more inclusive, and sustainable society in West Jakarta